L’évolution des négociations internationales sur le climat à l’heure de la COP 28 et leurs implications sur l’union européenne et sur le continent Africain - KHACHANI, Souad; MELLOUKI, Yousra; ALLAM, Lamya (International Journal of Business Intelligence, Management and Economics (IJBIME), 2024)
The text analyses developments in international climate negotiations, highlighting COP 28 and its impact on the European Union and Africa. It highlights climate change as a political, economic and social threat, supported by the conclusions of the United Nations IPCC. The poorest nations, lacking financial and technological resources, face difficulties in mitigating the effects of climate change. Industrialised countries, despite their power, sometimes fail to meet their commitments. The notion of "climate justice" is emerging, advocating an equitable distribution of the means to combat climate change. Although there have been some successes in the global fight against climate change, ethical questions persist in terms of equality of opportunity. The research methodology explores international legal instruments and the opinions expressed. The first part examines the evolution of the negotiations up to COP 27, while the second looks at the European Union’s contribution and its implications for Africa. Finally, the text highlights the importance of long-term climate data and interdisciplinarity in understanding the issues. Political decisions depend on the interactions between players, forces, lobbies and the media, which influence the fight against global warming.